Interplay Between Mitochondrial Oxidative Disorders and Proteostasis in Alzheimer’s Disease - Llanos-González, Emilio; Henares-Chavarino, Ángel Andres; Pedrero-Prieto, Cristina María; García-Carpintero, Sonia; Frontiñán-Rubio, Javier; Sancho-Bielsa, Francisco Javier; Alcain, Francisco Javier; Peinado, Juan Ramón; Rabanal-Ruíz, Yoana; Durán-Prado, Mario (Frontiers in Neuroscience, 2020)
Although the basis of Alzheimer`s Disease (AD) aetiology remain unknown, oxidative stress has been recognized as a prodromal factor associated to its progression. Oxidative stress refers to an imbalance between oxidants and antioxidants systems, which usually consists in an overproduction of reactive oxygen species (ROS) and reactive nitrogen species (RNS) that overwhelms the intrinsic antioxidant defences. Due to this increased production of ROS and RNS, several biological functions as glucose metabolism or synaptic activity are impaired. In AD, growing evidence link the ROS-mediated damages with molecular targets including mitochondrial dynamics and function, protein quality control system and autophagic pathways, affecting the proteostasis balance. In this scenario, oxidative stress should not only be considered as a major feature in the pathophysiology of AD but also a potential target to combat the progression of the disease. In this review, we will discuss the role of oxidative stress in mitochondrial dysfunction, proteins quality control systems and autophagy associated to AD and suggest innovative therapeutic strategies based on a better understanding of the role of oxidative stress and proteostasis.